Copper-Catalyzed Oxydifluoroalkylation of β,γ-Unsaturated Oximes for the Construction of Isoxazolines with a Difluoroalkyl Side Chain - Wang, Lianxin; Chen, Hongtai; Zhao, Wentao; Wang, Guangwei (Synlett, 2021)
A copper-catalyzed oxydifluoroalkylation of β,γ-unsaturated oximes has been developed. This reaction proceeded through a cascade of difluoroalkylation of alkene followed by a nucleophilic attack of the hydroxyl group of oximes. This protocol features mild reaction conditions, low-cost catalyst, and broad substrate scope, which provides a facile method to synthesize isoxazolines with a fluorinated side chain
Keywords: copper-catalyzed; oxydifluoroalkylation; isoxazoline; oximes; radical cyclization